2011
DOI: 10.1371/journal.pone.0019125
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Associated Nucleic Acid Hybridisation

Abstract: Nucleic acids promote amyloid formation in diseases including Alzheimer's and Creutzfeldt-Jakob disease. However, it remains unclear whether the close interactions between amyloid and nucleic acid allow nucleic acid secondary structure to play a role in modulating amyloid structure and function. Here we have used a simplified system of short basic peptides with alternating hydrophobic and hydrophilic amino acid residues to study nucleic acid - amyloid interactions. Employing biophysical techniques including X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 41 publications
2
53
0
1
Order By: Relevance
“…Moreover, oligomers are readily synthesized on certain mineral surfaces (Ferris 1996) and amyloid can spontaneously form fibrillar networks that acts as scaffolds for the amyloid assemblies themselves (Hamley 2007), as well as for other molecules, such as ribonucleotides (Liu et al 2008). Amyloid may also enhance the polymerization of ribonucleotides, and nucleic acids may enhance amyloid formation (Braun et al 2012). Of interest, in the context of the Cairns-Smith´s clay-as-genes hypothesis (Cairns-Smith 1982), is the observation that clay minerals can catalyze the formation of RNA (Wenhua and Ferris 2007).…”
Section: Prebiotic Amyloidogenesis: Surface-bound or In Solution?mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, oligomers are readily synthesized on certain mineral surfaces (Ferris 1996) and amyloid can spontaneously form fibrillar networks that acts as scaffolds for the amyloid assemblies themselves (Hamley 2007), as well as for other molecules, such as ribonucleotides (Liu et al 2008). Amyloid may also enhance the polymerization of ribonucleotides, and nucleic acids may enhance amyloid formation (Braun et al 2012). Of interest, in the context of the Cairns-Smith´s clay-as-genes hypothesis (Cairns-Smith 1982), is the observation that clay minerals can catalyze the formation of RNA (Wenhua and Ferris 2007).…”
Section: Prebiotic Amyloidogenesis: Surface-bound or In Solution?mentioning
confidence: 99%
“…Amyloid possesses the propensity to form self-propagating stable fibrillar networks that can act as scaffolds for nucleic acids ( Nandi andNicole 2004, Silva et al 2008) and other molecules, including lipids (Relini et al 2008, Domano andKinnunen 2008). Moreover, the amyloid surface can promote the polymerization of ribonucleotides, and nucleic acids may also enhance amyloidogenesis (Braun et al 2012). Importantly, amyloid-nucleic acid complexes enhance nucleic acid hybridization (Braun et al2012).…”
Section: Transition To An Rna Worldmentioning
confidence: 99%
“…39 Similarly, an amyloid formed from a basic peptide will have a higher affinity for the negatively charged backbone of a DNA molecule than a single peptide. 43 The wide species distribution and growing number of known functional amyloids is further evidence that despite its simplicity, the amyloid fold can give rise to a plethora of activities. 42 Finally, a feature that sets the amyloid structure apart with regard to a CA fold is that it can be formed by peptides as short as four amino acid residues, thus providing small peptides access to some features of larger folded proteins.…”
Section: Peptide Amyloidsmentioning
confidence: 99%
“…43,61 Interestingly, several studies have shown that there has been an evolutionary selection against β-aggregation-prone In each polymorph, the Glu side chain (yellow) exists in only one of two favored conformations. As in (a), there is an energy barrier (e.g., steric clashes) that prevents an individual from changing conformation on its own.…”
Section: Proteins As Genes: An Amyloid Replicator As the First Functimentioning
confidence: 99%
“…Such mutually beneficial effects have been shown for DNA and peptide amyloids, for which DNA stabilizes the amyloid fibers and the amyloid supports DNA hybridization (12). Furthermore, the encapsulation inside of vesicles by amphiphilic membrane-like structures may be beneficial to the encapsulated system by offering protection from hydrolysis and by preventing loss of the system through diffusion, as has been demonstrated for example by the chemical replication of RNA inside fatty acid vesicles (13) or by protein translation within vesicles that contain the 80 different macromolecular species required for translation (14).…”
Section: Introductionmentioning
confidence: 86%